Total parenteral nutrition prevents further nutritional deterioration in patients with cancer cachexia. - Bozzetti, F (1987)
The effects of total parenteral nutrition (TPN) on some nutritional variables were prospectively investigated in 12 severely cachectic patients with advanced cancer. The following variables were determined before and at 5-day intervals during the 20-day administration of TPN: anthropometric indices (body weight, arm circumference, triceps skinfold, arm muscle circumference, arm muscle area, arm fat area, total body muscle mass); biochemical indices (total protein, albumin, cholinesterase, total iron binding capacity, thyroxin-binding prealbumin, retinol binding protein, urinary 3-methylhistidine and creatinine excretion, nitrogen balance); and peripheral lymphocyte count. TPN was delivered at 49.5 nonprotein kcal/kg-1/day-1 (80% as dextrose and 20% as fat) and amino acids 1.9 g/kg-1/day-1. A significant increase was obtained in body weight, triceps skinfold, arm fat area, and retinol binding protein. All remaining anthropometric and biochemical parameters did not show any significant positive or negative change, although nitrogen balance remained positive. No significant liver toxicity was apparent after the TPN period. It was concluded that although TPN is unable to completely reverse some nutrition-related variables in cachectic patients with cancer, most patients were kept within a normal range and some improved. Therefore, further deterioration of the nutritional state, which is characteristic of this phase of disease, was at least prevented.